Healthcare workers’ mental health during the COVID-19 pandemic: a qualitative analysis of a text message-based NHS workforce support line - Richard Powell; Lisa Jane Gould; Eleanor Angwin; Emma Lawrance (BMJ Open)
Background The National Health Service (NHS) is suffering from a workforce crisis of mental and physical sickness and attrition following the COVID-19 pandemic. An in-depth understanding of healthcare workers’ (HCWs) experiences during the pandemic is required to understand the impacts on their mental health in this challenging work environment. This qualitative study explores HCWs’ concerns during the COVID-19 pandemic—expressed in real time during an active mental health crisis.Design This study involved analysis of data from ‘Shout’, a text message-based, UK-wide mental health support service which, during the pandemic, was advertised to HCWs specifically. Pseudorandom sampling of scripts of anonymised text message conversations between HCWs and Shout Volunteers from April 2020 to March 2021 was undertaken, with data fully anonymised by Shout before researchers accessed them on a secure purpose-built platform. Following application of exclusion and inclusion criteria, 60 conversations were coded to develop a thematic framework and analysed using grounded theory, with subthemes triangulated to create final themes. Quotes extracted from this process were then synthesised for publication.Results Three themes emerged from the data: (1) poor mental health, subthemes—(a) overwhelming negative feelings or emotional distress experienced, and; (b) active crisis/resurgent symptoms. (2) Negative work experiences, subthemes: (a) negative NHS work culture and expectations; (b) inadequate structures and arrangements for support; (c) trauma at work, and (d) abuse at work. (3) The impact of the COVID-19 pandemic, subthemes: (a) additional work pressure and (b) isolation and risk.Conclusion This study explores the challenges and mental health concerns in HCWs during an active crisis. Organisational stressors, mental health provision and additional resources for HCWs to recover from the pandemic remain a vital issue in current NHS service provision.